Correlational Study between Students' Reading Aloud Activity in the Classroom and Their Pronunciation - Ilhami El Husna; Senorica Yulia Sari (Universitas Negeri Padang, 2023)
This research was purposed to find out the correlation between students’ reading aloud activity in the classroom and their pronunciation. This research was correlational research. A total of 30 students of the nineth grade students in SMPN 1 Tanjung Baru were chosen using random sampling. Questionnaire and pronunciation test were used as the instruments to collect the data. The questionnaire was made up 20 close-ended questions related to reading aloud activity in the classroom while the test was a pronunciation test that the students had to read a text given by the researcher. According to the result of this research, the correlation coefficient is 1.000 which is higher than 0.05. It means that in SMPN 1 Tanjung Baru, there is no correlation between students’ reading aloud activity in the classroom and their pronunciation. According to further interview with the students as the sample of this research, the researcher found that the students did not feel that reading aloud activity in the classroom help them in their vocabulary, confidence, motivation, fluency, and reading comprehension since reading aloud activity was not applied well in the classroom. Even though the result of this research which was conducted in SMPN 1 Tanjung Baru is that there is no correlation between the two variables, this research was not purposed to generalize that the result of the research will be the same if it is conducted in other schools.